Empowering EFL Students’ Speaking Ability Through Digital Storytelling: A Quasi Experimental Study - Risqia Azizah; Iyan Irdiyansyah; Asih Wahyuni (Asshika: Journal of English Language Teaching and Learning, 2024)
Speaking ability is essential in 21st-century education, yet many students still struggle with limited vocabulary, unclear pronunciation, and low comprehension. This study examined the impact of two digital storytelling applications, Read to Me and Fairytales, on enhancing students’ speaking ability. A quantitative approach with a quasi experimental method are used in this research. The research was conducted at a private senior high school in Bogor using non-equivalent control groups design. Two tenth-grade classes were selected, both of classes chosen randomly by lottery system, with one group using Read to Me and the rest of the class using Fairytales. The research focused on speaking ability with the component vocabulary, pronunciation, and comprehension. The results were analyzed using an independent samples t-test, which showed a significant difference between the groups’ post-test scores (t = 2.32, df = 63, p < 0.05). The experimental group which is treated by Read to Me showed greater increased, likely due to features such as audio narration, highlighted text, and adjustable speed, which offered better language input. In conclusion, digital storytelling with interactive elements can effectively influences students’ speaking ability in phase E.